Interactive effects of mating receptivity and courtship pheromones on the scent preferences of female red-legged salamanders - Christy L. Kunkel; Karen M. Kiemnec-Tyburczy; Damien B. Wilburn (PLoS ONE, 2026)
The behavioral and endocrine responses elicited by pheromones are highly dependent on the sex and physiology of the receiving individual. In the red-legged salamander ( Plethodon shermani ), male courtship pheromones influence female mating behavior and regulate the timing of courtship. Pheromones also modulate female feeding behavior and scent preference in this species, but little is known about how the physiological state of females may influence their olfactory preferences. The aim of this study was to use laboratory trials to investigate whether differences in female receptivity influence the effect pheromones have on female scent preference. Our first experiment showed that pheromone treatment significantly increased the time females spent on male-scented substrate compared to both female scent and water. In a second experiment, female P. shermani with differing levels of mating receptivity were treated with either saline or pheromone and assayed for the relative time spent on each of three scents (male scent, food scent, and water). When females were treated with saline, their preference for male scent was positively correlated with mating receptivity. Application of pheromone also increased preference for male scent, but this effect was greater in females with lower receptivity. Pheromone treatment also decreased preference for food scent and was significantly pronounced in females with higher receptivity. These results suggest that courtship pheromones in P. shermani may have dual roles in regulating female preferences based on baseline mating receptivity, further suggesting a complex interplay between male courtship pheromones and female preference dynamics.